DIÁLOGOS ENTRE OS ESTUDOS DO COTIDIANO E A CULTURA VISUAL NA FORMAÇÃO DE PEDAGOGOS (Revista Apotheke, 2018)
This article constitutes from experiences as a teacher in the Distance Pedagogy course- CEAD / UDESC, reflecting on the importance of art education in the formation of future pedagogues. The reflections have as central points attention to daily life as learning development space as well as the importance of the sensitive eye education in this process. To do so, I construct this writing in a dialogical way with contributions and theoretical references related to the field of Visual Culture (HERNANDEZ, 2007, DIAS, 2011) and the Everyday Life Studies (ALVES, 1998; VICTÓRIO FILHO, 2005; PAIS, 2003), in order to think about how the teaching of art can help to form a closer and sensitive look at the knowledges that are developed in the daily actions that compose the educational spaces, contributing to the sensitive formation of these professionals.
Keywords: art teaching; teaching; everyday life studies; visual culture